2022
DOI: 10.1038/s41380-022-01826-x
|View full text |Cite
|
Sign up to set email alerts
|

A predictive ensemble classifier for the gene expression diagnosis of ASD at ages 1 to 4 years

Abstract: Autism Spectrum Disorder (ASD) diagnosis remains behavior-based and the median age of diagnosis is ~52 months, nearly 5 years after its first-trimester origin. Accurate and clinically-translatable early-age diagnostics do not exist due to ASD genetic and clinical heterogeneity. Here we collected clinical, diagnostic, and leukocyte RNA data from 240 ASD and typically developing (TD) toddlers (175 toddlers for training and 65 for test). To identify gene expression ASD diagnostic classifiers, we developed 42,840 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The PI3K/AKT signaling pathway is mainly involved in neural activities such as synaptic plasticity, neuronal development, memory consolidation, and protein synthesis [56]. The overexpression of the PI3K/AKT signaling pathway increases cell death, neuroinflammation, and oxidative stress leading to neurological diseases [57]. Research has shown that chrysophanol (CPH) can improve autismlike symptoms by inhibiting the PI3K/AKT/mTOR pathway [58].…”
Section: Neural Circuit Formation and Signal Pathwaymentioning
confidence: 99%
“…The PI3K/AKT signaling pathway is mainly involved in neural activities such as synaptic plasticity, neuronal development, memory consolidation, and protein synthesis [56]. The overexpression of the PI3K/AKT signaling pathway increases cell death, neuroinflammation, and oxidative stress leading to neurological diseases [57]. Research has shown that chrysophanol (CPH) can improve autismlike symptoms by inhibiting the PI3K/AKT/mTOR pathway [58].…”
Section: Neural Circuit Formation and Signal Pathwaymentioning
confidence: 99%
“…A diagnostic aid combining behavioural features from caregiver and healthcare provider questionnaires and home videos recently received regulatory approval by USA Food and Drug Administration (FDA) with sensitivity 98% and specificity 79% but had a high no response rate, 68% [ 8 ]. Other studies using magnetic resonance imaging (MRI) [ 9 ], visual attention/eye movement or eye tracking assessments [ 10 , 11 ], genetic mutation assessments [ 12 ] and post-natal blood tests for ASD based on transcriptomic analysis of peripheral blood mononuclear cells and proteomics and metabolomics analysis of plasma have been reported but require validation [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors play a dominant role in the etiology of autism. Despite this, a limited number of articles have specifically explained changes in genetic transcription in stratified studies of ASD age ( Rahbar et al, 2015 ; Bao et al, 2023 ). The neuropathological mechanism of autism is complex, involving abnormal synaptic function, abnormal neuronal activity patterns, abnormal genes, an abnormal immune system, etc.…”
Section: Introductionmentioning
confidence: 99%